Islam and Religion Plurality: Islam dan Pluralitas Agama - Amir Mahmud (Indonesian Journal of Islamic Education and Local Culture, 2023)
Islamic teachings value plurality or plurality as an unavoidable empirical reality. Each religion has different directions in carrying out worship or religious ceremonies. Understanding the activities of other religions besides those we profess within ourselves will foster an attitude of tolerance. Tolerance in religion does not mean we mix religious teachings, but respect each other and help create security and comfort for people of other religions in worship. Thus the plurality (diversity) of religion is a sunnatullāh that cannot be avoided in the life of society, nation, and state. In general, religion is the primary source of values in the culture. However, these values cannot change automatically manifest in the practice of human life. In other words, the values, ideas, and spirits introduced by religion, including Islam in it, are still passive. It must be distinguished between the wealth of treasures, thoughts, and religious principles contained in the holy book, or religious book, with the ability of its adherents or institutions to interact with the role of civilization. In that realm, conflicts of interest and assertion of identity will emerge on a different scale